Pfeiffer's classic activities for developing leaders : (Pfeiffer, 2003)
Good training builds good leaders. And there is no more powerful form of training than experiential learning. Pfeiffer's Classic Activities for Developing Leaders is a hands-on resource that offers twenty experiential learning activities, complete and ready to use in training sessions. These proven activities are designed to teach a wide variety of leadership skills to executives, managers, and supervisors. The book also includes questionnaires and surveys that measure everything from the leadership behaviors of individual trainees to organizational factors that influence or determine the way leadership will be exercised. Finally, the book contains insightful and informative articles that lay the educational foundation for the study of leadership as a teachable skill. The articles, experiential learning exercises, and questionnaires were specially selected as the best and most useful in the thirty-year history of the Pfeiffer Annuals. The tools in this kit are timeless, time-tested, and ready to be put to work in a large number of leadership-training situations.